Sécurité nationale et politique commerciale : analyse comparée de décisions américaines dans l'industrie de machines-outils (Note) - Roy, Martin (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1997)
This article seeks to illustrate how security considerations impact upon trade policy-making. In contrast to interpretations derived from hegemonic stability theory, this paper suggests that the shift from a bipolar to a multipolar world in the 1980s caused growing relative gains concerns within the Western alliance. Comparative analysis of American trade decisions in regard to the machine-tool industry shows that the change of decision between 1982 and 1986 regarding protection of the industry resulted from a change in political coalitions surrounding the demand of protection, which was caused by a transformation in the perception of national security. It is suggested that this uncertainty regarding the distribution of gains from trade is linked to the turn to unilateralism in American trade policy during the same period.